Transitioning to Highly Effective Therapies for the Treatment of Chronic Hepatitis C Virus Infection: A Policy Statement and Implementation Guideline - Daniel J Smyth; Duncan Webster; Lisa Barrett; Mark MacMillan; Lisa McKnight; Frank Schweiger (Canadian Journal of Gastroenterology and Hepatology)
Chronic hepatitis C virus (HCV) infection increases all-cause mortality, rates of cirrhosis, hepatocellular carcinoma, liver transplantation and overall health care utilization. Morbidity and mortality disproportionately affect individuals born between 1945 and 1975. The recent development of well-tolerated and highly effective therapies for chronic HCV infection represents a unique opportunity to dramatically reduce rates of HCV-related complications and their costs. Critical to the introduction of such therapies will be well-designed provincial programming to ensure immediate treatment access to individuals at highest risk for complication, and well-defined strategies to address the global treatment needs of traditionally high-risk and marginalized populations. HCV practitioners in New Brunswick created a provincial strategy that stratifies treatment according to those at highest need, measures clinical impact, and creates evaluation strategies to demonstrate the significant direct and indirect cost savings anticipated with curative treatments.